2010
DOI: 10.1002/bjs.6812
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a short-stay programme after breast cancer surgery

Abstract: : Introducing a care programme incorporating short stay following breast cancer surgery in four hospitals was feasible and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…In an earlier trial on oesophageal cancer patients, we found a similar working rate with 22/88 (25%) patients employed at diagnosis compared with 26% in this study 16. A recent trial on Dutch breast-cancer patients with a mean age of 55 years showed a higher employment rate at diagnosis of 49% 17. However, the patients in our study were much older with a mean age of 66 years.…”
Section: Discussionsupporting
confidence: 83%
“…In an earlier trial on oesophageal cancer patients, we found a similar working rate with 22/88 (25%) patients employed at diagnosis compared with 26% in this study 16. A recent trial on Dutch breast-cancer patients with a mean age of 55 years showed a higher employment rate at diagnosis of 49% 17. However, the patients in our study were much older with a mean age of 66 years.…”
Section: Discussionsupporting
confidence: 83%
“…Bundredet al (22) found no negative effect of early discharge on physical and psychological illness and advised early discharge for patients who were provided with informal care at home. In addition,the advantages of a short LOS includes less workload on staff, savings on hospital charges, reduction in waiting lists, and shift from expensive hospital care to cheaper home care (23). Bonnemaet al (16) reported major cost savings related to a shorter hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that efficient SF management in the early postoperative period is particularly important, since in the first 5 days after surgery wound healing mechanisms are initiated [5]. Besides, better control over SF may contribute to more common implementation of “the short-stay program” that has already been successfully introduced in a number of oncology centers [39]. In essence, shorter SF treatment improves patients’ quality of life.…”
Section: Discussionmentioning
confidence: 99%